PERKEMBANGAN ANAK TUNAGRAHITA DI SKH NEGERI 01 KOTA SERANG - Rifa Handayani; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the learning development of mentally retarded children at Special School (SKh) Negeri 01 Serang City. Children with intellectual disabilities require a different educational approach due to intellectual limitations that affect their ability to understand, remember and apply information. The research method used is a qualitative descriptive approach with observation, interviews and documentation as data collection techniques. The research results show that the learning development of mentally retarded children at SKh Negeri 01 Serang City is influenced by various factors, such as the teaching methods used, family support, and school facilities. Teachers play an important role in providing learning that is tailored to students' individual needs, such as the use of concrete learning media and direct practice approaches. Family support has also been proven to be significant in increasing children's learning motivation.